Assessment of Metal Impurity Partitioning and Speciation in Mineral Carbonation Processes Using FGD-Gypsum from Coal-Fired Power Plants under Distinct Operating Conditions - Córdoba, Patricia (ACS omega, 2024)
The sequestration of carbon dioxide (CO2) stands as a profoundly pivotal environmental challenge, given its potential to directly contribute to the advancement of environmental, societal, and economic objectives across a multitude of nations. In the present study, we have conducted an evaluation of the metal impurity partitioning and speciation in mineral carbonation processes conducted in laboratory using flue gas desulfurization (FGD) gypsums originating from both Spanish and two Chinese coal-fired power plants, each subject to distinct fuel sources and FGD operational conditions. Of the three resultant carbonation products, two exhibited CaCO3 content in the range of 81–83%, while the third registered 76.9% CaCO3 contenta variance attributed to the occurrence of metallic impurities within the initial FGD-gypsum. The partitioning and speciation of metal impurities at all stages of CO2 conversion have enabled us to proffer four potential reaction mechanisms governing carbonation efficiency: (i) conversion of metal sulfates to metal carbonate complexes, (ii) transformation of transferable elements into metal oxides and oxyhydroxide complexes, (iii) transformation of metal sulfates into diverse metal complexes, and (iv) diverse pathways of elemental transformation. Metal impurities present in FGD-gypsum lead to the formation of complexes between As and metals, thereby affecting their activity. Higher Ca/Mn, Ca/Fe, and Ca/Al ratios in one FGD-gypsum slurry enhance Ca3(AsO4)2·8H2O activity, while in another, excess Ca facilitates Mn3(AsO4)2·8H2O formation during carbonation, with coprecipitation retaining As in carbonation products. The occurrence of metallic contaminants in FGD-gypsums may exert a substantial influence on the effectiveness of CO2 conversion, thereby impacting the feasibility of using resultant carbonation products, with potential implications for environmental leaching and diminished reusability prospects.